Making Sense of a Scent-Sensing Metaphor for Microbes and Environmental Predictions - Jeff S. Bowman (American Society for Microbiology, 2021)
Microbes serve as sensitive indicators of ecosystem change due to their vast diversity and tendency to change in abundance in response to environmental conditions. Although we most frequently observe these changes to study the microbial community itself, it is increasingly common to use them to understand the surrounding environment.